The Metabolic Role of Peroxisome in Health and Disease - Basri İla, Hasan (Physiology, 2022)
Peroxisomes are cell organelles that have functions for the provision of homeostasis and sustainable cellular health. They are indispensable for lipid metabolism and free radical detoxification. A disruption in the peroxisomal pathway can cause irreparable problems or death for the organism. This book provides a comprehensive overview of peroxisomes, including their role in cell health and diseases such as cancer.